Effectiveness of international actors in debate of human rights in Iran 1990-2008. - Davoodifard, Hassan; Jawan, Jayum (INSInet Publication, 2011)
The Islamic Republic of Iran's (IRI) discourse and practice on human rights issues has raised much criticism in national and international levels. While Iranian government has had its own human rights perspective in treating its citizens, many international human rights organizations have campaigned to influence the behaviour of Iranian government and people in terms of development of human rights values in Iran. This study seeks to explore the role of international human rights actors related to promoting of human rights values in Iran from 1990-2008. It focuses on the role of international human rights actors such as European Union (UN), and international nongovernmental organizations (INGOs) such as Amnesty International (AI) and Human Rights Watch (HRW), and domestic Non-Governmental Organizations (NGOs) involved in promoting human rights in Iran. The findings of this study demonstrate that human right actors have played a significant role in the human rights situation in Iran. It also shows that the Iranian government and society have been affected by efforts of human rights actors after 1990.